Does the current state of biomarker discovery in autism reflect the limits of reductionism in precision medicine? Suggestions for an integrative approach that considers dynamic mechanisms between brain, body, and the social environment - Loth, Eva (Frontiers in Psychiatry, 2023)
Precision medicine approaches to autism were motivated by the recognition that a categorical diagnosis does not enable us to make accurate predictions about a particular autistic person’s development or their treatment/ support needs. It aims to tailor mechanism-based therapies to individual characteristics using biomarkers. The first set of biomarker studies created substantially larger, comprehensively characterised cohorts and shifted the focus from group-comparisons to individual variability and identifying subgroups. The goal of using biomarkers in the clinic prompted increased methodological rigour and analytic innovations. However, separate efforts to divide autism by molecular, brain structural/ functional or cognitive markers have not identified a clearly delineated diagnostic subgroup. Studies of monogenic forms of autism have revealed substantial variability in biology and behaviour. These findings may reflect limitations of current technologies but also of the predominant reductionist approach in biomedical science. Methodological reductionism seeks to parse complex issues into simpler, more tractable units and tends to divorce individuals from their social environment. Here it is proposed that we need to better understand additive and interactive effects between biological (brain, body) and social mechanisms (stress, stigma) to improve prognosis and tailored support. New studies require 1) closer collaboration with autistic people and families on the need and acceptance of different types of markers for particular purposes; 2) consideration of the context and conditions in which brain and cognition function and develop, and 3) cross-condition and multiplex family studies to identify mechanisms that are specific for particular autistic people or transdiagnostic across neurotypical and neurodiverse populations.